Power Equalizing Model for Financial Equity in Education Based on Islamic Values - Andry Syahrul (AFKARINA: Jurnal Pendidikan Agama Islam, 2024)
This research explores how the power-equalizing model in educational financial management can increase fund allocation efficiency and transparency by integrating key elements, including stakeholder participation, the use of technology, and innovative economic management strategies. The research method involved interviews with participants, educators, educational managers, and technology developers to identify best practices and challenges faced in implementing this model. The findings show that the power equalizing model in financial management can improve transparency and accountability in fund management. Still, stakeholder coordination and technology adaptation challenges need to be addressed further. The conclusions of this research emphasize the importance of integrating innovative elements in educational and financial management to achieve better efficiency and fair allocation of funds.